2015
DOI: 10.7441/joc.2015.02.04
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of SME Competitiveness in Indonesia

Abstract: The purposes of this study are to analyze source of SME competitiveness in selected industry clusters in Indonesia and to develop a theoretical model of SME competitiveness. This study employs quantitative design with multivariate model. We develop three models of estimation by using multiple regression analysis. Our models are based on Porter Model of Competitiveness (1990) which contains factor condition, demand condition, related and supporting industries and business strategy. Findings in this study idennt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 30 publications
2
15
0
2
Order By: Relevance
“…The external factors consist of market competition, legal and political conditions, and social and cultural environment including the language used to communicate with consumers. The internal factors are including brand management, marketing strategies, top management support, the effectiveness of deployment of human resources, and innovation are key factors, especially in the high-growth South-East Asia region (Anton et al, 2015). However, SMEs have a unique characteristic such as limited financial and human resources (Abdullah et al, 2010;Tambunan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The external factors consist of market competition, legal and political conditions, and social and cultural environment including the language used to communicate with consumers. The internal factors are including brand management, marketing strategies, top management support, the effectiveness of deployment of human resources, and innovation are key factors, especially in the high-growth South-East Asia region (Anton et al, 2015). However, SMEs have a unique characteristic such as limited financial and human resources (Abdullah et al, 2010;Tambunan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of 76 developed and developing countries by Ayyagari et al (2007) showed that SMEs are solely responsible for the creation of about 60 percent of employment in manufacturing sector. Moreover, SMEs also help improve socioeconomic conditions of a country by reducing import and producing products locally by fulfilling the needs of local community (Straka et al, 2015;Setyawan et al, 2015). Regardless of their significant contribution to the economy, the survival rate of SMEs is significantly lower than of large corporate firms due to various reasons, including restricted access to bank finance, high interest rates, lack of skilled labour forces, existence of technological and financial risks, severe competition from large firms etc.…”
Section: Introductionmentioning
confidence: 99%
“…Companies that are able to produce good quality products or services are effective companies in the sense that they will be able to compete. Several studies have measured the competitiveness of SMEs by using indicators containing factor conditions, demand conditions, related and supporting industries and business strategies (Anton, Muzakan, & Muhammad, 2015). The measure of competitiveness in SMEs in this study uses organizational capability, competency of the owners and the performance of SMEs (Hudson, Smart, & Bourne, 2001), (Darsono, Yahya, & Amalia, 2016), (Ramadhilla Maghfira Utami and Donald Crestofel Lantu, 2013) and (Nota & Santander, 2012).…”
Section: Results and Findingsmentioning
confidence: 99%
“…Hamdani, Maulani, & Muharam, 2019) 2000-2020 Driven factors (N. A. Hamdani, Nugraha, & Suparman, 2020), (Carrasco, Carrington, & Lee, 2009) Furthermore (Anton et al, 2015) explains the theoretical concepts of SME competitiveness (Kadocsa, 2006). Several studies explain the importance of information technology in SMES (Ladokun IO, Osunwole OO, & Olaoye BO, 2013), (Windrum & De Berranger, 2010) and (N. A.…”
Section: Yearmentioning
confidence: 99%